Pilot trial of upcycling of MSWI fly ash into mineral wool: Effects of fluxing agents on vitrification, viscosity and heavy metal immobilization - Yike Zhang; Zengyi Ma; Mengxia Xu; Jingqi Sun; Bingyi Zhang; Jiadong Zhang; Penglin Ma; Jianhua Yan (Case Studies in Construction Materials)
Upcycling municipal solid waste incineration fly ash (MSWI-FA) into mineral wool offers a sustainable solution for both safe disposal and resource recovery of hazardous waste. Given the high calcium and low silica, alumina and magnesia content of MSWI-FA, the addition of fluxing agents (SiO2, Al2O3, and MgO) is essential for optimizing vitrification and material properties. This study employs a four-factor, three-level orthogonal experimental design to systematically examine how these fluxing agents influence vitrification, melt viscosity, and heavy metal immobilization. Results indicate that SiO2 content above 30 wt% and Al2O3 content between 10 and 15 wt% act as effective network formers, promoting the formation of Q2 and Q3 silica tetrahedra, and enhancing heavy metal retention, albeit with higher melt viscosity and production temperatures. Conversely, MgO and MSWI-FA function as network modifiers, disrupting Si-O-Si and Si-O-Al bonds, thereby reducing viscosity, lowering fiberization temperature, and broadening the operation window for mineral wool formation. Pilot trials using four-roller centrifugal spinning confirm that the optimized MSWI-FA-derived mineral wool exhibits excellent thermal and fire-resistant properties, and economic assessment confirms its positive economic benefits, underscoring its potential for large-scale application. Collectively, these findings provide new insights into the structural influence of fluxing agents and substantiate the feasibility of producing high-quality mineral wool from MSWI-FA through controlled vitrification.